2010
DOI: 10.1002/app.32775
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 1,2 units content on the hydrogenation of polydienes by TSH

Abstract: The influence of 1,2 vinyl content on hydrogenation of SBR and BR rubbers with high molecular weight by a noncatalytic method using p-toluenesulfonylhydrazide (TSH) as reagent was investigated. Results show an increase of hydrogenation percentage with molar ratio of the reagents, temperature, and reaction time. The degree of hydrogenation depends strongly on the microstructure of the rubber mainly on the amount of 1,2 content. Infrared spectroscopy (FTIR) was used to confirm the microstructural characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Catalytic hydrogenation is the conventional one, but it has some drawbacks such as: ( i ) the high cost of the equipment, ( ii ) the use of expensive hydrogenation conditions, which are mostly associated with high pressure reactors and expensive catalyst, and ( iii ) the low efficiencies resulting from limited solubility of the reagents. Alternatively, the hydrogenation of unsaturated polymers by a non-catalytic way, in which the reaction is promoted by diimide (diazene, NH=NH), has been shown to be an attractive process and extremely efficient in the case of 1,3-diene polymers [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic hydrogenation is the conventional one, but it has some drawbacks such as: ( i ) the high cost of the equipment, ( ii ) the use of expensive hydrogenation conditions, which are mostly associated with high pressure reactors and expensive catalyst, and ( iii ) the low efficiencies resulting from limited solubility of the reagents. Alternatively, the hydrogenation of unsaturated polymers by a non-catalytic way, in which the reaction is promoted by diimide (diazene, NH=NH), has been shown to be an attractive process and extremely efficient in the case of 1,3-diene polymers [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…exert the decisive effect on the properties of PB. The relationship between the parameters (c, t, v) and properties of PB is still at the focus of researchers' attention [3][4][5][6][7]. In this case, the question arises as to whether the determination of the above parameters is correct [6].…”
mentioning
confidence: 95%
“…With regards to the properties of SBS and hydrogenated SBS, it has been demonstrated that the composition of the elastomeric block and the overall copolymer architecture play an important role in determining their thermal and mechanical properties .…”
Section: Introductionmentioning
confidence: 99%